2021
DOI: 10.1590/1414-431x2020e10669
|View full text |Cite
|
Sign up to set email alerts
|

Isolated obesity resistance condition or associated with aerobic exercise training does not promote cardiac impairment

Abstract: Mechanisms involved in cardiac function and calcium (Ca 2+ ) handling in obese-resistant (OR) rats are still poorly determined. We tested the hypothesis that unsaturated high-fat diet (HFD) promotes myocardial dysfunction in OR rats, which it is related to Ca 2+ handling. In addition, we questioned whether exercise training (ET) becomes a therapeutic strategy. Male Wistar rats (n=80) were randomized to standard or HFD diets for 20 weeks. The rats were redistributed for the absence or presence of ET and OR: con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 41 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…In addition to the incredible ability to resist the development of obesity, the OR model may have cardioprotective characteristics and protection against metabolic disorders, for example, lipotoxicity [ 1 ]. These characteristics were also observed in the current study, in which OR rats showed maintenance of glycemic control, normal insulin and improvement in the lipid profile evidenced by normal glycemic values during the glucose tolerance test and higher HDL values, indicating a probable cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the incredible ability to resist the development of obesity, the OR model may have cardioprotective characteristics and protection against metabolic disorders, for example, lipotoxicity [ 1 ]. These characteristics were also observed in the current study, in which OR rats showed maintenance of glycemic control, normal insulin and improvement in the lipid profile evidenced by normal glycemic values during the glucose tolerance test and higher HDL values, indicating a probable cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Kleiner et al [ 38 ], using transgenic mice knockouts for PPARγ co-activator and gene transcription co-activator 1α (PGC1α), an important co-activator of mitochondrial biogenesis, demonstrate reduced oxidative capacity and insulin resistance [ 38 ]. As mentioned above, this seems to be one of the responses for the protective capacity of OR animals against the development of metabolic and cardiometabolic disorders [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations